Altered Dynamic Postural Stability and Joint Position Sense Following British Army Foot-Drill - Rawcliffe, Alex J.; Hinde, Katrina L.; Graham, Scott M.; Martindale, Russell; Morrison, Andrew; Krajewski, Kellen T.; Connaboy, Chris (Frontiers in Sports and Active Living, 2020)
Impaired proprioceptive acuity negatively affects both joint position sense and postural control and is a risk factor for lower-extremity musculoskeletal injury in athletes and military personnel. British Army foot-drill is an occupational military activity involving cyclical high impact loading forces greater than those observed in athletes during high level plyometrics. Foot-drill may contribute to the high rates of lower-extremity overuse injuries observed in recruits during basic training. There is limited research investigating foot-drill specific injury risk factors in women. This study aimed to quantify changes in ankle joint proprioception and dynamic postural stability following a period of British Army foot-drill. Fourteen recruit age-matched women underwent pre-post foot-drill measures of frontal plane ankle joint position sense (JPS) and dynamic postural stability using the dynamic postural stability index (DPSI). Passive ankle JPS was assessed from relative test angles of inversion (IN) and eversion (EV) 30% and IN60% using an isokinetic dynamometer. The DPSI and the individual stability indices (medio-lateral [MLSI], anterior-posterior [APSI] and vertical [VSI]) were calculated from lateral and forward jump-landing conditions using force plates. Foot-drill was conducted by a serving British Army drill instructor. Significantly greater absolute mean JPS error for IN30% and EV30% was observed post foot-drill (p ≤ 0.016, d ≥ 0.70). For both the lateral and forward jump-landing conditions, significantly greater stability index scores were observed for MLSI, APSI and DPSI (p ≤ 0.017, d ≥ 0.52). Significantly greater JPS error and stability index scores are associated with the demands of British Army foot-drill. These results provide evidence that foot-drill negatively affects lower-extremity proprioceptive acuity in recruit age-matched women, which has implications for increased injury risk during subsequent military physical activity, occurring in a normal training cycle.